Pelatihan Peningkatan Tumbuh Kembang Anak dalam Kemampuan Berbahasa sebagai Dampak Masa Pandemi Covid-19 bagi Guru dan Orang Tua: Training to Improve Child Development in Language Skills as Impact of the Covid-19 Pandemic for Teachers and Parents - Perla Yualita; Sajodin Sajodin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The Covid-19 pandemic has significantly impacted life, including the growth and development of children in language skills. Few parents and teachers, especially at the Early Childhood Education level, complained that their children were hampered in language skills (speaking). Therefore, training is needed for teachers and parents to stimulate children's language skills. The purpose of this PkM is to increase the knowledge of teachers and parents about children's growth and development so that they are willing and able to stimulate children's language skills. Methods of implementation: a) analysis of the situation with partners, b) implementation of pre-test, c) provision of materials, 4) implementation of post-test and evaluation of activities. The results of the PkM show increasing in the knowledge of teachers and parents about the growth and development of children's language skills by 75.48 with a significance value of 0.000> 0.05. Thus, in general, teachers and parents are equipped with the knowledge to improve children's language skills due to the Covid-19 pandemic. In addition, the teachers and parents seemed to give a positive response. The positive response is evident from the enthusiasm and attendance of 72.83% of participants despite the rainy weather from early morning until the PkM ended.